Who Benefits From Being an Only Child? A Study of Parent–Child Relationship Among Chinese Junior High School Students - Liu, Yixiao; Jiang, Quanbao (Frontiers in Psychology, 2021)
After more than three decades of implementation, China’s one-child policy has generated a large number of only children. Although extensive research has documented the developmental outcomes of being an only child, research on the parent-child relational quality of the only child is somewhat limited. Using China Education Panel Survey (2014), this study examined whether the only-child status was associated with parent-child relationships among Chinese junior high school students. It further explored whether children’s gender moderated the association between the only-child status and parent-child relationships. Two-level ordered logit models suggested that only children were more likely to report a close relationship with their mothers and fathers compared to children from multiple-child families (including two-child families). Taking birth order into consideration, we found that, only children were more likely to have close parent-child relationships than firstborns, whereas no significant differences were found between only children and lastborns. Interaction analyses further suggested that the only-child advantages were gender-specific: the positive effects of the only-child status were stronger for daughters than for sons, that is, daughters benefited more from being only children. Our findings highlight the importance of considering children’s gender and birth order in exploring the only-child effects. Additional analyses about sibling-gender composition indicated female children were more likely to be advantaged with the presence of younger brothers, whereas male children benefited more from having older sisters. This reveals that the son preference culture is still deep-rooted in Chinese multiple-child families.